THE ROLE OF FOCAL INTERVENTION IN HUMANIZING CARE AND PROMOTING TREATMENT ADHERENCE: AN EXPERIENCE REPORT IN A HOSPITAL SETTING (PRÁXIS EM SAÚDE, 2025)
The presented experience report stems from the Mandatory Internship in the Surgical Clinic of a University Hospital, addressing the role of the psychologist in the hospital context. Given the high patient turnover, there arose a need for the psychologist to adapt to the hospital environment. In this context, brief and focal interventions were employed. The described case involved a 51-year-old male patient who was resistant to Total Parenteral Nutrition (TPN) due to misinformation. The psychological intervention included psychoeducation, mediation of communication with the medical team, and the body scanning technique, promoting treatment adherence and reducing emotional distress. Hospitalization often generates stress and anxiety, intensified by ineffective communication from the healthcare team. In this context, focal interventions and psychoeducation proved essential to facilitate patient adaptation, minimize emotional impacts, and strengthen humanized care. It is concluded that the psychologist’s role in the hospital environment significantly contributes to treatment adherence and psychological well-being, being a fundamental tool in comprehensive health care.
Keywords: Focal Interventions; Psychoeducation; Health Humanization; Hospital Psychology; Treatment Adherence